Refleksi Pembelajaran Tasawuf Selama Pandemi Covid-19 Di IAIN Kediri - Hafil, Ach. Shodiqil (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
One of the aspects affected by the Covid-19 pandemic is education. In this case, we arerequired to adapt quickly so that this epidemic does not paralyze the education aspect.When schools and universities do not allow face-to-face classes, online learning is an alternative that we must accept with all the consequences. In learning Sufism at IAIN Kediri, it is also necessary to find out how to provide effective online lectures so that they are able to achieve the expected results. Moreover, learning Sufism is part of character education that demands integration and interconnection between understanding, habituation and example. This study, which is a descriptive-analytical reflection, has resulted in the finding that during the Covid-19 pandemic, Sufism lecturers and students must play their roles well and meaningfully. Educating the community in a Sufi way is expected to provide a solution. At least this way can reconcile a heart that is troubled because of fear and anxiety that is endless. Remembering Allah in every action and thought makes people realize that there is nothing that is not wise. There is wisdom behind this worrying pandemic. There is wisdom behind the troublesome online lectures. There is wisdom in every effort made. There is wisdom behind the hope that is raised.